Phonological answers to orthographic problems. On the treatment of non-sibilant obstruent + liquid groups in Hispano-celtic (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2019)
This paper argues that the only way to spell non-sibilant obstruent + liquid groups in the Hispano-Celtic adaptation of the semisegmental, semi- moraic Iberian script was through the use of a so-called ‘dead’ vowel that anticipates the colour of the following etymological vowel, e.g., Tiŕiś = /tri:s/. Orthographies that evince a metathesis, e.g., ConTeŕPia beside Latinised loc. sg. CONTREBIAE, or do not spell the liquid at all, e.g., ConTePias, are not alternative ways of representing such groups, but are indicative of real sound changes, viz., metathesis and deletion of a consonant in coda position before another consonant. Cross-linguistic evidence is presented in favour of such an analysis.